ACEHNESE AWARENESS OF PHYSICAL DISTANCING POLICY DUE TO COVID-19 - Angga Syahputra; Devi Nurtiyasari; Zani Anjani (Jurnal Analisa Sosiologi, 2021)
Corona Virus Disease 2019 (Covid-19) has spread to more than 190 countries around the world. Covid-19 in Indonesia was first reported on March 2, 2020, i.e. as much as 2 cases. As of June 12, 2020, there were 36.406 confirmed cases (positive) and 2048 deaths cases. In Aceh, as of June 12, 2020, there were 115 total cases with 20 confirmed cases (positive) and 1 death case. In dealing with Covid-19, Indonesia Government has issued various policies based on studies of expertise and direction from the World Health Organization (WHO). One of the policies is to implement Physical Distancing. This policy becomes a challenge to be implemented in Indonesia. The Aceh Provincial Government also urged citizens to implement this policy. This study conducted to see the factors affecting Acehnese awareness in implementing Physical Distancing policy. The result shows that it is significantly affected by job factor, whereas other factors such as age and salary have no significant effect. Keywords: Covid-19; Society Awareness; Public Awareness; Physical Distancing AbstrakVirus Covid-19 telah menyebar ke lebih dari 190 negara di dunia. Covid-19 di Indonesia pertama kali dilaporkan pada 2 Maret 2020 yaitu sebanyak 2 kasus. Hingga 12 Juni 2020, terdapat 36.406 kasus terkonfirmasi (positif) dan 2048 kasus kematian. Di Aceh, per 12 Juni 2020, terdapat total 115 kasus dengan 20 kasus terkonfirmasi (positif) dan 1 kasus kematian. Dalam menangani Covid-19, Pemerintah Indonesia telah mengeluarkan berbagai kebijakan berdasarkan kajian keahlian dan arahan dari Organisasi Kesehatan Dunia (WHO). Salah satu kebijakannya adalah dengan menerapkan physical distancing social. Kebijakan ini menjadi tantangan untuk diterapkan di Indonesia. Pemerintah Provinsi Aceh pun mengimbau warganya menerapkan kebijakan ini. Penelitian ini dilakukan untuk melihat faktor-faktor yang mempengaruhi kesadaran masyarakat Aceh dalam menerapkan kebijakan menjaga jarak fisik. Hasil penelitian menunjukkan bahwa faktor pekerjaan dipengaruhi secara signifikan, sedangkan faktor lain seperti umur dan gaji tidak berpengaruh signifikan. Kata Kunci: Covid-19; Kesadaran Masyarakat; Kesadaran Publik; Jarak Fisik.